Alignment of diet prescription to genotype does not promote greater weight loss success in women with obesity participating in an exercise and weight loss program. (26th November 2018) - Coletta, A. M.; Sanchez, B.; O'Connor, A.; Dalton, R.; Springer, S.; Koozehchian, M. S.; Murano, P. S.; Woodman, C. R.; Rasmussen, C.; Kreider, R. B.
Summary: Objective: Genetics contribute to variability in individual response to weight‐loss interventions. The objective of this study was to determine the efficacy of a commercially available exercise and weight‐loss program and whether alignment of diet to genotype related to lipid metabolism promotes greater success. Design: Sedentary women with obesity ( n  = 63) had genotype (FABP2rs1799883, PPARG2rs1801282, ADRB3rs4994C3, ADRB2rs1042713, rs1042714) determined using a direct‐to‐consumer genetic screening kit purported to promote greater weight‐loss success through dietary recommendations based on these genes. Participants were randomly assigned to follow a moderate carbohydrate (MC) or lower carbohydrate (LC) hypo‐energetic diet that aligned (A) or did not align (NA) with genotype for 24 weeks while participating in a resistance training and walking program. Data were analysed by general linear model repeated measures adjusted for baseline variables and are presented as mean (95% confidence interval) changes from baseline. Results: Participants in the LC group experienced greater improvements ( p  = 0.051, ηp 2  = 0.025) in per cent changes in body composition (weight: MC −3.32 [−1.4, −5.2], LC −5.82 [−4.1, −7.6]; fat mass: MC −7.25 [−3.2, −11.2], LC −10.93 [−7.3, −14.5]; fat‐free mass: MC −0.32 [1.4, −2.0], LC −1.48 [0.7, −3.0]; and body fat percentage: MC −4.19 [−1.6, −6.8], LC −5.60 [−3.3, −7.9] %). No significant differences were observed between genotype groups (weight: A −5.00 [−3.3, −6.7], NA −4.14 [−2.2, −6.1]; fat mass: A −10.15 [−7.0, −13.6], NA −8.02 [−4.0, −12.0]; fat‐free mass: A −1.23 [0.3, −2.8], NA −0.56 [1.12, −2.3]; and body fat: A −5.28 [−3.0, −7.6], NA −4.51 [−1.9, −7.1] %). Conclusions: Adherence to this exercise and weight‐loss program promoted improvements in body composition and health outcomes. While individuals following the LC diet experienced greater benefits, alignment of these diets to this genetic profile did not promote greater health outcomes.